Ignition of wood subjected to the decreasing radiant energy flux; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Kuznetsov V. T.; Filkov A. I.; Isaev Yu. N. Yusup Niyazbekovich; Guk V. O. (2015, 2015)
Title screen